2019
DOI: 10.1038/s41467-019-09053-9
|View full text |Cite
|
Sign up to set email alerts
|

In-host evolution of Staphylococcus epidermidis in a pacemaker-associated endocarditis resulting in increased antibiotic tolerance

Abstract: Treatment failure in biofilm-associated bacterial infections is an important healthcare issue. In vitro studies and mouse models suggest that bacteria enter a slow-growing/non-growing state that results in transient tolerance to antibiotics in the absence of a specific resistance mechanism. However, little clinical confirmation of antibiotic tolerant bacteria in patients exists. In this study we investigate a Staphylococcus epidermidis pacemaker-associated endocarditis, in a patient who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 59 publications
1
56
0
Order By: Relevance
“…Loss of Agr function has previously been described as a contributing factor in infections caused by Staphylococcus sp .. It appears to contribute towards a phenotype furthering immune evasion, such as increased biofilm formation and reduced production of PSMs [ 43 46 ]. We did not observe any non-synonymous SNPs (nsSNPs) or small insertions or deletions in agrBDCA .…”
Section: Resultsmentioning
confidence: 99%
“…Loss of Agr function has previously been described as a contributing factor in infections caused by Staphylococcus sp .. It appears to contribute towards a phenotype furthering immune evasion, such as increased biofilm formation and reduced production of PSMs [ 43 46 ]. We did not observe any non-synonymous SNPs (nsSNPs) or small insertions or deletions in agrBDCA .…”
Section: Resultsmentioning
confidence: 99%
“…However, the high tolerance of CoNS biofilm cells commonly causes the failure of antibiotics, even when the most severe therapies are used [214] and, in the cases associated with the use of IMD, may implicate the removal of the infected device, resulting in prolonged hospital stays and increased morbidity and mortality rates [42,203,215]. Interestingly, the problematic of IMD-associated infections was emphasized by a recent study that assessed S. epidermidis in-host evolution in a case of pacemaker-associated endocarditis, which has shown that increased tolerance to antibiotics and capacity to form biofilms occurred during the course of infection [216]. This helps to explain the often inefficacy of antibiotics to treat S. epidermidis infections.…”
Section: Antibiotic Resistancementioning
confidence: 99%
“…This will further increase the time duration required for killing the bacterial population. Recent clinical studies have shown in-host evolution of antibiotic tolerance in other pathogenic bacteria and its association with treatment complications (21).…”
Section: Introductionmentioning
confidence: 99%